Perempuan Dayak Mali: Melindungi Alam dari Maut - Nikodemus Niko (Universitas Padjadjaran, 2017)
This study describes the everyday life of the Dayak Mali and their attempt to build a strong attachment to their natural environment and their aim to preserve it before and after the establishment of palm-oil plantation in West Kalimantan. The strong attachment between Dayak Mali women and their natural environment exemplifies women’s-nature relationships found in many ecofeminism studies; in which women are often assumed as the representation of the nature due to their strong attachment to the nature. This study applied qualitative method. It found that Dayak Mali women’s have built their strong attachment to their natural environment and they also continuously preserve their culture and tradition in protecting their natural environment amid the fast growing of palm-oil and mining plantation industry. However, despite their important role in natural preservation, the Dayak Mali women, continuously marginalized in the government policy due to their poverty and powerlessness, Keyword: Women, Community, Dayak Mali